Histopathology Test in Dyslipidemic Female White Rats (Rattus Norvegicus) Treated With Chitosan Nanoparticle Gel of Pineapple Peel Extract (Ananas Comosus (L.) Merr) as Anti-Cellulite - Indri Merista; Aisa Dinda Mitra; Camila Putri Firira (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Cellulite is considered a skin condition associated with aging appearance due to the accumulation of fat deposits beneath the skin. The use of natural-based skincare products, such as pineapple peel extract containing active compounds, offers an alternative solution for reducing cellulite. Pineapple peel contains beneficial bioactive compounds, including flavonoids, tannins, saponins, bromelain enzymes, and secondary metabolites such as quercetin, which act as lipolytic agents. This study aimed to determine the effect of varying concentrations of pineapple peel extract gel and chitosan nanoparticle–based pineapple peel extract gel on their anti-cellulite effectiveness and to identify the gel formulation that meets good physical quality requirements. The research employed an experimental method, beginning with sample collection, determination, simplicia preparation, extraction using maceration, phytochemical screening, nanoparticle solution formulation, and gel formulation with various concentrations (F0 0%, F1 2.5%, F2 5%, F3 2.5%, and F4 5%). The gel formulations were evaluated for their physical properties, including organoleptic characteristics, homogeneity, pH, spreadability, adhesiveness, and stability, followed by a histopathological test on the skin. The results show that all gel formulations exhibit physical characteristics that meet standard quality requirements. The variation in gel concentration influences the histopathological outcomes in female dyslipidemic white rats with cellulite, where an increased concentration of chitosan nanoparticle gel up to 5% significantly reduces the number of fat cells and improves skin tissue structure.